Clinical Utility of Droplet Digital PCR to Monitor BCR-ABL1 Transcripts of Patients With Philadelphia Chromosome–Positive Acute Lymphoblastic Leukemia Post-chimeric Antigen Receptor19/22 T-Cell Cocktail Therapy - Guan, Yuqi; Zhang, Meilan; Zhang, Wei; Wang, Jiachen; Shen, Kefeng; Zhang, Kai; Yang, Li; Huang, Liang; Wang, Na; Xiao, Min; Zhou, Jianfeng (Frontiers in Oncology, 2021)
Philadelphia chromosome–positive acute lymphoblastic leukemia (Ph+ ALL) accounts for 20-30% of adult ALL patients, characterized by translocation of t (9; 22). Tyrosine kinase inhibitors (TKIs) has significantly improved the outcome even though there are still some problems including relapse due to drug-resistant mutations and suboptimal molecular remission depth. Previously, we reported the safety and efficacy of sequential infusion of CD19/22 CAR-T cells immunotherapy in treatment of relapsed/refractory (R/R) B-cell neoplasms including Ph+ ALL cases. Given possible deeper reaction, more patients were expected to reach optimal minimal residual disease (MRD) response. An alternative method, duplex droplet digital PCR (ddPCR) with high sensitivity was established, which could provide absolute quantification of MRD without the need for calibration curves. Here, we retrospectively collected 95 bone marrow samples from 10 R/R Ph+ patients, who received 19/22 CAR-T cell cocktail therapy. Notably, SMR3, a significant indicator based on ddPCR after CAR-T fusion was established, which was defined as sequential molecular remission for no less than 3 months with negative MRD. In this cohort, no recurrence was observed in six patients achieving SMR3, four of whom accepted allogeneic hematopoietic stem cell transplantation (allo-HSCT) after CAR-T cell regimen. Unfortunately, the other four patients who didn’t reach SMR3 relapsed, and didn’t receive extra specific treatment except CAR-T regimen. To sum up, ddPCR may be an alternative especially when nucleic acid were insufficient in clinical practice. No achievement of SMR3 may be an early warning of potential relapse after CAR-T and indicating the initiation of other therapies including allo-HSCT.